Marketing Channel Efficiency Analysis of Birds eye Chili Commodity in Grabag District Magelang Regency - Muhammad Syahmi Wumu; Migie Handayani; Edy Prasetyo (Faculty of Animal and Agricultural Science, Diponegoro University, 2026)
Bird’s eye chili (Capsicum frutescens L.) is a high-value horticultural commodity with strong economic potential for farmers in Indonesia. Grabag District, located in Magelang Regency, is one of its main production centers. However, inefficiencies in the marketing system—such as long distribution chains and middlemen dominance—often reduce farmers' income. This study aims to analyze the marketing channel patterns of bird’s eye chili in Grabag, assess their efficiency using marketing margin, farmer’s share, and marketing efficiency, and identify factors influencing marketing efficiency. The research was conducted through surveys from November 2024 to February 2025, involving 150 farmers selected through two-stage cluster sampling and five marketing institutions selected using snowball sampling. Data analysis included descriptive statistics, one-sample t-tests, and multiple linear regression. The results showed two main marketing channels: channel I (involving auction groups and collectors) and channel II (only collectors). Both channels were considered efficient, with efficiency values of 2.37% and 2.44%, respectively. Channel II provided the highest farmer’s share at 84%. Furthermore, producer price, marketing cost, channel type, and sales volume had a significant effect on efficiency (p < 0.05). This study highlights the importance of improving institutional support and simplifying marketing chains to enhance the bargaining power and welfare of chili farmers. Channel II is recommended as the most efficient option.